Improving coronary artery bypass grafting (CABG) skills through virtual reality simulations: reducing errors in surgical training - Hafeez, Alisha; Rafay, Muhammad Abdul; Huzafa Ali (Journal of the Pakistan Medical Association, 2025)
Dear Madam, Virtual reality (VR) is an emerging technology that utilizes artificial intelligence (AI) - powered graphics to create realistic simulations. One of the most critical objectives in medical education is to optimize the quality of training and practical proficiency, and also to minimise errors. Coronary Artery Bypass Grafting (CABG) is a complex surgical procedure that involves a high level of technical expertise, as even minor deviations can have a substantial detrimental effect on patient outcomes. As a result, VR emerges as a valuable tool in the healthcare system, improving patient rehabilitation, surgical accuracy, and healthcare worker training, particularly for complex operations such as CABG. VR (Virtual Reality) can be used by Surgeons to precisely plan minimally invasive treatments using in situ artery grafts by employing virtual reality to evaluate patient-specific anatomy before surgery in CABG. Virtual reality makes it easier to evaluate anatomical features precisely before surgery and improves graft design planning. In a study employing 3D VR for minimally invasive CABG, 100% graft patency, no early complications, and a 7.1-day recovery were observed, with the surgical plan modified in just 11.8% of cases(1). An analysis of research conducted between 2000 and 2021 found that there is strong evidence to support the use of immersive virtual reality (VR) in surgical training, with improvements in procedure times, accuracy, user satisfaction, and cost-effectiveness(2). VR training can also help reduce surgical errors by increasing physicians’ competence, which improves decision-making, skills, and knowledge, and results in safer surgeries(3). Virtual reality (VR), particularly in cardiac surgery training, has gained significant popularity in recent years.. By reducing surgical error rates by 40%, virtual reality training has been shown to improve patient safety and the overall efficacy of the healthcare system(4)Hence, Virtual reality, along with dry-lab simulations, can transform medical education by providing advanced resources for procedural training, re-credentialing, and pre-operative planning. It is seen to improve accuracy, lower surgical errors, and refine techniques, especially for complex procedures such as coronary artery bypass grafting Integrating VR into medical training will make surgeries safer, recovery times shorter, and patient outcomes better.